Analisis Efektivitas Biaya dan Waktu dalam Rantai Pasok Transportasi Berbasis Teknologi GPS pada Perusahaan Logistik - Dzaky, Muhammad Haekal; Harimurthi Wulandjani, Syamsurizal Syamsurizal , Erwin Permana, (STIE AMKOP, 2025)
The supply chain is the backbone of business operations. With good supply chain management, businesses can be more stable, competitive, and capable of long-term growth. Research on supply chains in large companies has been widely conducted. However, studies on cost and time efficiency in transportation supply chains for companies in general have not been extensively explored. This research was conducted using a qualitative descriptive approach. The data for the study was obtained through digital tracing and observations from various official sources and related official websites. The results of the study show that by implementing a GPS-based supply chain, Agung Raya achieved time and operational efficiency. The efficiency improvements not only reduced operational costs but also enhanced service reliability and customer satisfaction. With better visibility in logistics distribution, Agung Raya significantly reduced the risk of delivery delays and provided more accurate and up-to-date information to customers regarding shipment status. Additionally, it strengthened connectivity among key elements in the supply chain—vehicles, drivers, and cargo—which ultimately led to overall operational efficiency improvements. The implementation of IoT solutions and integrated data management enabled the company to achieve substantial cost savings, accelerate delivery cycles, and enhance the reliability of logistics services. This strategic move not only strengthened Agung Raya’s competitive position in the transportation industry but also provided significant added value to customers through more transparent and responsive services tailored to their needs Keywords: Effectiveness, Cost, Time, Supply Chain, Transportation